1998 Annual Conference Proceedings
DOI: 10.18260/1-2--7235
|View full text |Cite
|
Sign up to set email alerts
|

Internship Experiences In Biomedical Engineering Technology: An Overview Of Students And Prospective Employers Perceptions

Abstract: Students pursuing an Associates Degree in Biomedical Engineering Technology at Penn State University are required to complete a 400-hour internship in an approved health care facility before graduation. This paper analyzes how the students perceive the need to be involved in the internship, including its effect on their professional development as well as on their ability to perform the tasks associated with their responsibilities. The students were asked to describe and summarize their experiences in the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Other benefits to supervisors and departments identified in the survey include a temporary expansion of staffing, helping to promote the field, the possibility of learning different troubleshooting techniques from the intern, and having the opportunity to assist a new biomed in getting their career started and figuring out their interests. The benefits to students identified here align well with those discussed in previous studies [2]- [4], [6], as do a number of the identified benefits to supervisors [3], [6]. A few benefits to supervisors were not highlighted in previous publications, such as the supervisor learning new troubleshooting methods from the intern and opportunities to promote and grow the field.…”
Section: Benefits and Challengessupporting
confidence: 84%
See 2 more Smart Citations
“…Other benefits to supervisors and departments identified in the survey include a temporary expansion of staffing, helping to promote the field, the possibility of learning different troubleshooting techniques from the intern, and having the opportunity to assist a new biomed in getting their career started and figuring out their interests. The benefits to students identified here align well with those discussed in previous studies [2]- [4], [6], as do a number of the identified benefits to supervisors [3], [6]. A few benefits to supervisors were not highlighted in previous publications, such as the supervisor learning new troubleshooting methods from the intern and opportunities to promote and grow the field.…”
Section: Benefits and Challengessupporting
confidence: 84%
“…There are few studies, for example, that focus on the benefits of the internship to the internship supervisors and the organizations they represent. While scholars recognize that mutual benefit is a goal of internship practices, most of the published studies focus on contributions the students make to the supervision site, ranging from picking up extra workload, motivating staff members to get involved in professional activities, and gaining a stronger appreciation for the skill sets that new hires bring to the table, such as relieving work load and motivating staff members (at the supervision site) to get involved [3], [6]. Part of the relative lack of scholarly attention may not be due to lack of interest.…”
Section: Benefits Of Internshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, almost no research has been conducted on student success pathways in biomedical engineering technology [2], [3], a gap this study seeks to fill with a mixed-methods study of student engagement and persistence in an introductory biomedical engineering technology course.…”
Section: Introduction/ Literature Reviewmentioning
confidence: 99%